2022
DOI: 10.1002/agg2.20305
|View full text |Cite
|
Sign up to set email alerts
|

Short‐term corn yield response associated with nitrogen dynamics from fall‐seeded cover crops under no‐till dryland conditions

Abstract: The availability of in‐season N to corn (Zea mays L.) following fall‐seeded cover crops depends on seasonal patterns of nitrogen (N) transformations that are site‐ and year‐dependent and resist prediction. Our objectives were to evaluate N dynamics following different cover crops (legume, nonlegume, none) and their relationship with subsequent corn yields within an established no‐till winter wheat (Triticum aestivum L.)–cover crop/corn–soybean (Glycine max) rotation over two site‐years in the U.S. Northern Pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 41 publications
0
1
1
Order By: Relevance
“…2010) the use of winter rye cover crop provided bene cial relationships different than those previously described following winter rye use. Speci cally, we found that corn yields increased with increased N mineralization following cover crop application, which contrasts previous research using winter rye (Chim et al 2022). The increases in kernel count driven by N-mineralization-associated enzyme activities supports our hypothesis for coupling a cover crop with dredged sediments for agricultural use, which is the goal of using soil amendments in agricultural systems.…”
Section: Nutrient Dynamics Drive Corn Biomass and Productioncontrasting
confidence: 99%
See 1 more Smart Citation
“…2010) the use of winter rye cover crop provided bene cial relationships different than those previously described following winter rye use. Speci cally, we found that corn yields increased with increased N mineralization following cover crop application, which contrasts previous research using winter rye (Chim et al 2022). The increases in kernel count driven by N-mineralization-associated enzyme activities supports our hypothesis for coupling a cover crop with dredged sediments for agricultural use, which is the goal of using soil amendments in agricultural systems.…”
Section: Nutrient Dynamics Drive Corn Biomass and Productioncontrasting
confidence: 99%
“…Additionally, cover crop application was not bene cial for photosynthetic e ciency as e ciency was signi cantly greater in the control plot left fallow during vegetative development and decreased over time regardless of treatment. Responses for corn grown in dredged sediments following cover crop application varied from those documented within non-dredged sediment amended agricultural systems, with many bene ts missing(Mahama et al 2016; Acharya et al 2020;Chim et al 2022). Although corn yield was the only plant response to bene t from cover crop application due to changes in soil properties, the combination of cover crop application with dredged sediments may be bene cial but not necessary to improve corn production.Soil Properties Differ in Response to Cover Crop ApplicationSeveral dredged sediment soil properties failed to signi cantly vary between the cover crop and non-cover crop plots.…”
mentioning
confidence: 99%